Cuidado centrado no usuário: vivências da equipe de saúde e dos usuários em um serviço de nefrologia hospitalar - Martins, Graziele Alves (2025)
This study aims to understand the experiences of both the healthcare team and users regarding User-Centered Care (UCC) in a hospital nephrology service. The specific objectives are: to identify the characteristics of UCC from the perspectives of users and healthcare professionals; to analyze the principles of UCC through experience reports from the healthcare team and users; and to describe the limitations of implementing UCC in the context of hospital nephrology. This is a qualitative study using thematic analysis, conducted in the nephrology department of a hospital located in the countryside of São Paulo State, Brazil. Eight users and twelve healthcare professionals from various disciplines were interviewed in July 2024. The thematic content analysis was based on the theoretical framework of UCC, drawing from the works of Carl Rogers, Stewart, and authors inspired by Michael Balint. The results led to the construction of five empirical categories, based on interview analysis, which reveal key characteristics of UCC: a close, humanized relationship between users and healthcare professionals; users’ understanding of their illness through clear communication and health education in the nephrology service; a holistic understanding of the person through integrated, network-based care; strategies for collaboratively building the care plan; and limitations to the implementation of user-centered care in hospital nephrology. Furthermore, both professionals and users shared similar reports highlighting the user’s active participation in care within the sector. The healthcare professionals emphasized the importance of users understanding each step of the assistance provided in the nephrology department, noting that each individual has a particular way of engaging with this process. As a limitation, they pointed to challenges in adapting to staff rotation, especially among nursing technicians and nurses.The study concludes that when properly implemented, UCC in hospital nephrology leads to greater user satisfaction and increased professional fulfillment. This approach requires the integration of users' preferences and goals into therapeutic decisions, recognizing the importance of open and continuous dialogue between healthcare professionals and the individuals receiving care.